Ma.Po.Ci. pēcukiṟār : varalāṟṟu mukkiyattuvam vāynta coṟpoḻivukaḷ - Civañāṉam, Ma. Po., 1906- (Iṉpa Nilaiyam, 1980)
Lectures, chiefly on the educational system in Tamil Nadu, politics, and Tamil literature.